1995
DOI: 10.1002/hep.1840210131
|View full text |Cite
|
Sign up to set email alerts
|

Concanavalin A—induced T-cell—mediated hepatic injury in mice: The role of tumor necrosis factor

Abstract: Concanavalin A activates T lymphocytes in vitro and causes T-cell-dependent hepatic injury in mice. T lymphocytes were previously identified as effector cells of concanavalin A-induced liver injury. Here we report that hepatic injury is characterized by apoptotic cell death. On concanavalin A challenge, the cytokines tumor necrosis factor-alpha (TNF alpha), interleukin-2, granulocyte macrophage-colony stimulating factor, and interferon-gamma were detectable in the circulation of the mice. Pretreatment of mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
428
2
2

Year Published

1997
1997
2006
2006

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 271 publications
(454 citation statements)
references
References 56 publications
22
428
2
2
Order By: Relevance
“…Our present observation that immunoinflammatory hepatitis can be induced in mice by a single i.v injection of Con A further confirms the original data by Tiegs' group [1,2], which were independently reproduced by others [3,8]. Most histological and immunopathogenic pathways described in those studies were also observed here.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our present observation that immunoinflammatory hepatitis can be induced in mice by a single i.v injection of Con A further confirms the original data by Tiegs' group [1,2], which were independently reproduced by others [3,8]. Most histological and immunopathogenic pathways described in those studies were also observed here.…”
Section: Discussionsupporting
confidence: 92%
“…An additional control group consisted of mice challenged only with PBS (Table 1). Because marked increases of transaminase activity along with severe histological signs of hepatic injuries have been reported to develop 8 h after Con A injection in these mice [1,2], the animals were killed after 8 h, and blood and livers were collected. Table 1.…”
Section: Mice and Hepatitis Inductionmentioning
confidence: 99%
“…These data are corroborated by a recent report from YodaMurakami and co-workers showing an increase of adiponectin in inflamed liver tissue induced by injection of CCl 4 [10]. ConA-induced hepatic inflammation is characterized by highly elevated systemic as well as hepatic TNF-a levels [11]. In addition, adiponectin has been shown to be a major antagonist of TNF-a production in several cell types [7,12].…”
Section: Discussionsupporting
confidence: 73%
“…ConA-induced hepatitis is also thought to be a model of immunologically induced hepatocyte injury, and its histological features resemble those of viral-or drug-induced acute hepatitis in humans. 1,7,[25][26][27][28][29][30] In this mode, hepatocyte cell death induced by ConA is caused by necrosis and apoptosis. Hence, apoptosis and Th1 cytokine release were thought to be key factors.…”
Section: Discussionmentioning
confidence: 99%
“…4 We also know that the stimulation of Fas on hepatocytes by anti-Fas antibodies causes severe damage to hepatocytes by apoptotic cell death. 31 Earlier results showed that liver necroapoptosis induced by ConA is mediated by TNF-a and IFN-g. 1,4,5,7,[25][26][27][28][29][30]32 On TNF-a receptor crosstalk, the death domain of the TNF-a receptor 1 associates with TNF receptor 1-associated protein (TRADD), causing Fas-associated death domain (FADD) recruitment. FADD in turn activates upstream caspase-8, and the effector caspases involved in apoptosis, caspase-9 and -3.…”
Section: Discussionmentioning
confidence: 99%